2015
DOI: 10.18632/oncotarget.4301
|View full text |Cite
|
Sign up to set email alerts
|

Dose coverage of axillary level I-III areas during whole breast irradiation with simplified intensity modulated radiation therapy in early stage breast cancer patients

Abstract: PurposeThis study was designed to evaluate the dose coverage of axillary areas during whole breast irradiation with simplified intensity modulated radiation therapy (s-IMRT) and field-in-field IMRT (for-IMRT) in early stage breast cancer patients.MethodsSixty-one consecutive patients with breast-conserving surgery and sentinel lymph node biopsy were collected. Two plans were created for each patient: the s-IMRT and for-IMRT plan. Dosimetric parameters of axillary areas were compared.ResultsThe average of mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…In case of axillary coverage by 3D-CRT, the study of Kataria et al, [ 16 ] and this study showed relatively similar mean dose and values of V 40, V 45 , and V 47.5 in the lower axilla area (level I and II). However, the values for the same parameters reported by Zhang et al [ 17 ] were too low compared to those of Kataria et al and this study. This difference might be due to differences in patient position, contouring extent of the axilla, field extent, and/or IMRT optimization.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In case of axillary coverage by 3D-CRT, the study of Kataria et al, [ 16 ] and this study showed relatively similar mean dose and values of V 40, V 45 , and V 47.5 in the lower axilla area (level I and II). However, the values for the same parameters reported by Zhang et al [ 17 ] were too low compared to those of Kataria et al and this study. This difference might be due to differences in patient position, contouring extent of the axilla, field extent, and/or IMRT optimization.…”
Section: Discussioncontrasting
confidence: 89%
“…They concluded that the s-IMRT plan delivered a lower dose to the axilla, and thus caution should be exercised for the centers using the s-IMRT technique. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to Kataria et al, who did not impose a dose-volume constraint on the axilla, as in the present study, when comparing IMRT (two tangential semi-opposed beams with gantry angles of 130-145 and 305-320 for the medial and lateral fields, respectively) with 3D-CRT (tangential beams with the same angles and orientations as IMRT), the incidental axillary irradiation with IMRT was lower than with 3D-CRT at levels I and II (19). Zhang et al also imposed no constraint on the axilla and compared between conformal techniques such as simplified-IMRT (s-IMRT; five to seven beams) with forward IMRT (for-IMRT; two tangential opposite beams with the field-in-field technique) (33). The unintended dose to the axilla, especially level I, was lower with s-IMRT than for-IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…It has the fewest degrees of freedom to modulate the dose delivery patterns. At the other extreme is the intensity-modulated radiation therapy (IMRT), which uses inverse planning and dynamic multileaf collimator (MLC) to generate plans with optimized dynamic fluence [20, 21]. However, the use of IMRT will substantially increase the cost to patients and workload to physicians, physicists and dosimetrists [22, 23].…”
Section: Discussionmentioning
confidence: 99%